Teori Pendidikan Keluarga dan Tanggung Jawab Orang Tua dalam Pendidikan Anak Usia Dini - Jailani, M. Syahran (NADWA, 2014)
This paper describes the responsibilities of parents in early childhood education. From the review of the literature it is known that the family environment be-comes a major place of a child to education. Father and mother in the family becomes the first educators in the process of development of a childs life. Par-ents do not just build a relationship and do various family for reproductive pur-poses, continue descent, and establish affection. The main task of the family is to create buildings and atmosphere of family education process so that the next generation of intelligent and noble generation as a solid footing in the tread life and the journey of human children. The fact is supported by the findings of the theories that support the importance of family education as the first basic educa-tion of children.